The Inventory of Personality Organization: A valid instrument to detect the severity of personality dysfunction - Unoka, Zsolt; Csáky-Pallavicini, Krisztina; Horváth, Zsolt; Demetrovics, Zsolt; Maraz, Aniko (Frontiers in Psychiatry, 2022)
Background and aims In the eleventh revision of the International Classification of Diseases (ICD-11), the severity of personality dysfunction became the central dimension of personality disorder’s (PDs) definition, besides the trait domain qualifiers. Personality functioning, also known as personality organization (PO), is becoming an increasingly important concept in administering, predicting, and measuring severity and nature of personality disturbance. Otto Kernberg and his team developed several tools to measure personality impairment. The Inventory of Personality Organization (IPO) is a self-report rating scale for the measurement of PO. Aim of this study was to identify severity groups according to the level of PO and to explore their validity. Materials and methods A clinical sample of 118 patients was recruited from a 4-weeks in-patient cognitive psychotherapy program. Beside the IPO, Structured Clinical Interview for the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders, (DSM-IV.) Axis I and II, Symptom Check List-90 (SCL-90), State-Trait Anger Expression Inventory and Dissociative Experience scale (DES). Two types of analyses were conducted: a person-centered (latent profile) analysis and various variable-centered tests to confirm the factor structure of IPO and calculate group differences. Results The three-factor (CFI = 0.990, TLI = 0.990, RMSEA = 0.022, SRMR = 0.089) and the five-factor (CFI = 0.995, TLI = 0.995, RMSEA = 0.014, SRMR = 0.090) models of the IPO was supported. Latent class analysis identified three subgroups of PO: “Well-integrated,” “Moderately integrated,” and “Disintegrated” classes. There were no significant differences between the three classes in the number of Axis 1 diagnoses (p = 0.354; η2 = 0.01). Group differences in the number of PDs, the number of PD symptoms as well as in the presence of borderline and depressive PD were significant (all p < 0.001; V = 0.35–0.42; η2 = 0.15–0.26). Persons with more severe PO problem level had higher rates of psychopathological symptoms, state and trait anger, and dissociative characteristics (all p < 0.001; η2 = 0.13–0.36). Conclusion The IPO can be an appropriate instrument to measure the severity of personality disorganization and to classify participants along a continuum of severity in this regard. Our results present further evidence that the severity of personality dysfunction, the central dimension of the ICD-11 and the Alternative Model for PDs is detectable with an instrument, the IPO, that was initially developed to detect the disturbances in PO.